Hederasaponin C Alleviates Lipopolysaccharide-Induced Acute Lung Injury In Vivo and In Vitro Through the PIP2/NF-κB/NLRP3 Signaling Pathway - Han, Shan; Yuan, Renyikun; Cui, Yushun; He, Jia; Wang, Qin-Qin; Zhuo, Youqiong; Yang, Shilin; Gao, Hongwei (Frontiers in Immunology, 2022)
Gene transcription is governed by epigenetic regulation that is essential for the pro-inflammatory mediators surge following pathological triggers. Acute lung injury (ALI) is driven by pro-inflammatory cytokines produced by the innate immune system, which involves the nod-like receptor 3 (NLRP3) inflammasome and nuclear factor-κB (NF-κB) pathways. These two pathways are interconnected and share a common inducer the phosphatidylinositol 4,5-bisphosphate (PIP2), an epigenetic regulator of (Ribosomal ribonucleic acid (rRNA) gene transcription, to regulate inflammation by the direct inhibition of NF-κB phosphorylation and NLRP3 inflammasome activation. Herein, we report that hederasaponin C (HSC) exerted a therapeutic effect against ALI through the regulation of the PIP2/NF-κB/NLRP3 signaling pathway. In lipopolysaccharide (LPS)/ lipopolysaccharide + adenosine triphosphate (LPS+ATP)-stimulated macrophages, our results showed that HSC remarkably inhibited the secretion of interleukin-6 (IL-6), IL-1β, and tumor necrosis factor-α (TNF-α). Moreover, HSC inhibited NF-κB/p65 nuclear translocation and the binding of PIP2 to transforming growth factor-β activated kinase 1 (TAK1). The intracellular calcium (Ca2+) level was decreased by HSC via the PIP2 signaling pathway, which subsequently inhibited the activation of NLRP3 inflammasome. HSC markedly alleviated LPS-induced ALI, restored lung function of mice, and rescued ALI-induced mice death. In addition, HSC significantly reduced the level of white blood cells (WBC), neutrophils, and lymphocytes, as well as pro-inflammatory mediators like IL-6, IL-1β, and TNF-α. Hematoxylin and eosin (H&E) staining results suggested HSC has a significant therapeutic effect on lung injury of mice. Interestingly, the PIP2/NF-κB/NLRP3 signaling pathway was further confirmed by the treatment of HSC with ALI, which is consistent with the treatment of HSC with LPS/LPS+ATP-stimulated macrophages. Overall, our findings revealed that HSC demonstrated significant anti-inflammatory activity through modulating the PIP2/NF-κB/ NLRP3 axis in vitro and in vivo, suggesting that HSC is a potential therapeutic agent for the clinical treatment of ALI.